Cytotoxicity of Cryptochlorogenic acid against Breast cancer cell line (MCF7) isolated from Moringa oleifera Leaves Cultivated in Iraq - Banan Kareem Bedewi; Ghaith Ali Jasim; Ibrahim Saleh Abbas; BasmaTalib Al-Sudani (College of Pharmacy / Mustansiriyah University, 2022)
oleifera L., a Moringaceae family is fast-growing tree. M. oleifera's dried leaves are Characterized with high in phenolic compounds. phenolic compounds have anti-cancer, anti-microbial, anti-inflammatory, anti-allergic and antioxidant activities. Therefore, The current study involved isolation Cryptochlorogenic acid by preparative TLC from M.oleifera leaves grown in Iraq,  and study its cytotoxicity effect against a breast cancer cell line (MCF7) using the MTT cell viability assay, and comparing it to a standard anticancer drug (Tamoxifen). The isolated Cryptochlorogenic acid was cytotoxic to the MCF7 cell line, with an IC50 of 20.8M.